Environmental Design as A Modern Design Direction - Kodirova Sh.B. (Genius Journals, 2021)
Educational articles consecrated by the research of the development of the design, its personality, principles, and also the same. A man, surrounded by a covered room, will take the peace of his house.
Keywords: Natural environment; environmentally friendly materials; woods; plants